Common test methods for cables under fire conditions. Tests on gases evolved during combustion of materials from cables. Procedures. Determination of degree of acidity of gases for cables by determination of the weighted average of pH and conductivity Part 2-3, (15th September 1999) - British Standards Institution,
No abstract available